Hymenochaete yaoshanensis sp. nov. (Hymenochaetaceae, Hymenochaetales), a wood-inhabiting fungus from Yunnan Province, southwest China - Xu, Xiumei; Li, Mei; Feng, Jian; Chen, Meng; Deng, Yinglian; Zhao, Changlin; Shen, Shan (Phytotaxa, 2026)
The fungi constitute a highly diverse group distinct from plants and animals, and accurately determining the taxonomic placement of newly discovered taxa is essential for understanding fungal evolution and ecological function. In this study, a new species, Hymenochaete yaoshanensis, is proposed based on a combination of morphological features and molecular evidence of ITS and nLSU. The phylogenetic analysis inferred from ITS+nLSU sequence data placed H. yaoshanensis within the family Hymenochaetaceae and showed it to be closely related to H. pinnatifida and H. longispora. Hymenochaete yaoshanensis is characterized by a tuberculate to locally verruculose hymenial surface, a monomitic hyphal system, slightly thick-walled generative hyphae with simple septa, and oblong ellipsoid basidiospores (4–6 × 2–3 µm). A full description, illustrations, and phylogenetic analysis are provided to facilitate future taxonomic and systematic studies of Hymenochaete taxa.